Efecto del pelado enzimático sobre el perfil sensorial de diferentes variedades de naranja - Budde, Claudio Olaf; Gabilondo, Julieta; Garitta, Lorena Verónica; Pieroni, Victoria (Instituto de Tecnología de Alimentos, INTA, 2023)
Citrus are fruits that present great advantages for minimal processing (MP) due to its physiological and morphological characteristics¹ . Enzymatic peeling is one of the methods used to obtain citrus MP; over the years it was optimized and adapted to the different species and factors that influence the quality of the final product such as adherence of the skin to the fruit, of the segments to each other, thickness of the skin and by the appearance of the bitter taste caused by limonene². All of these factors can compromise the sensory quality of the product.